2010
DOI: 10.1164/rccm.200912-1805oc
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Age

Abstract: Rationale: Healthy aging is associated with cognitive deficits similar to those found in obstructive sleep apnea (OSA). As in OSA, older adults show compensatory cerebral activation during cognitive demands in the face of neurocognitive decline. Objectives: The current study examines whether the combination of increasing age and sleep apnea will lead to a stronger compensatory response than either factor alone, or overwhelm the brain's capacity to compensate. Methods: A total of 14 treatment-naive patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…The study by Ayalon et al ., 2010 has recently shown that the combined effects of SDB and aging produced significant impairments in cognitive function and neural activation, greater than either variable acting independently [17]. These data are also in accordance with the findings obtained from an aging animal model of OSA, where exposure to chronic intermittent hypoxia produced impaired special learning and increased neural apoptosis in older rats [18].…”
Section: Discissionsupporting
confidence: 82%
“…The study by Ayalon et al ., 2010 has recently shown that the combined effects of SDB and aging produced significant impairments in cognitive function and neural activation, greater than either variable acting independently [17]. These data are also in accordance with the findings obtained from an aging animal model of OSA, where exposure to chronic intermittent hypoxia produced impaired special learning and increased neural apoptosis in older rats [18].…”
Section: Discissionsupporting
confidence: 82%
“…It is possible that the older adult with lifelong subclinical untreated SDB has developed a compensatory tolerance for its effects, or “pre-conditioning” and therefore does not exhibit associated cognitive disturbance[56]. It is also possible that the older adult with lifelong subclinical untreated SDB has reached a threshold whereby normal age-associated neurodegenerative processes render them no longer able to withstand the impact of SDB on cognition, resulting in significant cognitive impairment and decline in ability to care for self [9, 52]. Neither of these hypothetical scenarios considers the impact of new onset SDB in the older adult, which the epidemiological literature suggests is highly widespread [1].…”
Section: Discussionmentioning
confidence: 99%
“…

Double Insult Hypothesis . Case-controlled prospective studies should examine the “double insult” hypothesis [52] of SDB-associated cognitive dysfunction in older adults. Alchanatis and colleagues [28] and Mathieu and colleagues [27] reported somewhat contradictory findings using optimal study designs to address the question of whether the cognitive deficits observed in older adults with SDB are of similar or greater magnitude than those observed in middle and younger aged adults with SDB and normal control subjects.

…”
Section: Considerations For Future Research On Sdb-related Cognitive mentioning
confidence: 99%
“…Ayalon et al (2010) demonstrate that the presence of OSA accelerates the age-related decline in cognitive performances in middle-aged patients (>45 years) showing a decreased activation of the frontal gyrus, hippocampus, and parietal lobe during a sustained attention and a verbal encoding task. These results are supported by a morphological study (Torelli et al, 2011) showing a correlation between age and volumes of the total and left hippocampus, amygdale, and brain parenchyma in OSA patients.…”
Section: Cognitive Function In Elderly Osa Subjectsmentioning
confidence: 99%